The Transformation of the Paradigm of Islamic Science at State Islamic Universities as a Response to the Challenges of Globalization and the Industrial Revolution 4.0 - Peri Gunawan; Mohamad Yudiyanto; Nanat Fatah Natsir; Erni Haryanti; Diansyah Permana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore and understand the transformation of the knowledge paradigm at Syarif Hidayatullah and Sunan Kalijaga State Islamic Universities (UIN) and its relevance to the Fourth Industrial Revolution. This transformation responds to the need to integrate modern science and technology with Islamic values as an effort to form an intellectual generation ready to face the challenges of globalization and the Fourth Industrial Revolution. The methodology applied includes a literature review and a comparative approach to understand the integration models adopted by both universities. This transformation is expected to contribute significantly to creating an adaptive curriculum that maintains Islamic identity in the digital era.